2007
DOI: 10.1016/j.pain.2006.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of exercise for chronic whiplash-associated disorders

Abstract: Whiplash-associated disorders are common and incur considerable expense in social and economic terms. There are no known effective treatments for those people whose pain and disability persist beyond 3 months. We conducted a randomized, assessor-blinded, controlled trial at two centres in Australia. All participants received 3 advice sessions. In addition the experimental group participated in 12 exercise sessions over 6 weeks. Primary outcomes were pain intensity, pain bothersomeness and function measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 14 publications
2
126
1
6
Order By: Relevance
“…24,25 To our knowledge, only one previous randomized controlled trial 11 of patients with chronic WAD included Grade III patients. The results of the present study show that there is an urgent need for increased knowledge of the best way to treat this subgroup of WAD patients, suggesting that future randomized controlled trials should also include patients with Grade III WAD.…”
Section: Wad Gradementioning
confidence: 99%
See 2 more Smart Citations
“…24,25 To our knowledge, only one previous randomized controlled trial 11 of patients with chronic WAD included Grade III patients. The results of the present study show that there is an urgent need for increased knowledge of the best way to treat this subgroup of WAD patients, suggesting that future randomized controlled trials should also include patients with Grade III WAD.…”
Section: Wad Gradementioning
confidence: 99%
“…2 In recent studies, up to 50% of WAD patients 3,4 and 30% to 100% of postsurgical CR patients 4-9 report personal suffering from prolonged symptoms, with persistent pain, disability, and reduced health-related quality of life (HRQoL). Physical function and treatment have been severely understudied both for CR patients scheduled for surgery 9,10 and for chronic WAD patients, 11 particularly for patients with verified neurological and musculoskeletal findings (WAD Grade III). 11 Evidence of effective physiotherapy is inconclusive because there have been few randomized controlled trials involving these specific groups of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four large randomized controlled trials were identified in the literature [13][14][15][16]. Stewart et al [13] compared a 6-week general exercise and cognitive behavioral program to professional advice of encouragement to resume light activity alone. They found a short-term improvement immediately after treatment in the group with combined exercise and behavioral training.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 and 6 months, improvements were reported in the two groups that performed NSE when compared to the group that received only a prescription for physical activity. More understanding of the role of NSE as a treatment for WAD is still needed [13,16] to improve rehabilitation potential in patients with more severe problems (WAD grade 3).…”
Section: Introductionmentioning
confidence: 99%